2011
DOI: 10.1007/s10530-011-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Linaria dalmatica invades south-facing slopes and less grazed areas in grazing-tolerant mixed-grass prairie

Abstract: Identifying environments where invasive plants are most invasive is key to understanding causes of invasion and developing effective management strategies. In mixed-grass prairie, invasive plants are often successful in relatively wet, nitrogen-rich areas, and areas protected from grazing. Dalmatian toadflax, a common invader of mixed-grass prairie, can also be favored by high water and nitrogen availability, but is thought to be relatively unpalatable to cattle, and therefore favored by grazing. We used spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Linaria dalmatica was also modeled as most likely to occur in open areas dominated by grasses and in areas with reduced vegetative cover but more roads or other human-created disturbances. This agrees with published studies describing L. dalmatica invasion (e.g., Blumenthal et al 2012;Vujnovic and Wein 1997).…”
Section: Predicted Invasive Ranges For Linaria Dalmatica and Linaria supporting
confidence: 93%
“…Linaria dalmatica was also modeled as most likely to occur in open areas dominated by grasses and in areas with reduced vegetative cover but more roads or other human-created disturbances. This agrees with published studies describing L. dalmatica invasion (e.g., Blumenthal et al 2012;Vujnovic and Wein 1997).…”
Section: Predicted Invasive Ranges For Linaria Dalmatica and Linaria supporting
confidence: 93%
“…Linaria dalmatica is a short-lived, herbaceous perennial that primarily invades well-drained, coarse-textured soils and is commonly associated with disturbed, sparsely vegetated habitats including roadsides, gravel pits, fields, waste areas, rockslides and other sloped areas (Robocker 1974;Vujnovic & Wein 1997;Blumenthal et al 2012). Seeds can germinate in the fall but more commonly germinate in the spring, and seedling establishment is higher in open areas devoid of competition (Grieshop & Nowierski 2002).…”
Section: S T U D Y S Y S T E Mmentioning
confidence: 99%
“…Both progressive invasion of the site and treatment effects could also have been influenced by other processes, such as grazing management or changing climate, both of which can affect plant invasion in this ecosystem (Harmoney , Blumenthal et al. , , Prevey and Seastedt ). These temporal patterns demonstrate that invasion can take considerable time to become apparent following composted manure addition to otherwise undisturbed perennial grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work at this site has suggested that cattle grazing can inhibit invasive species, likely by favoring competitive grass species (Blumenthal et al. ). Grazing effects on B. tectorum could differ, however, due to its distinct early‐season phenology, which limits exposure to grazing.…”
Section: Methodsmentioning
confidence: 96%